Hepatoprotective Screening of Seriphidium kurramense (Qazilb.) Y.R. Ling. (6th December 2021) - Ali, Maroof; Hussain, Hidayat; Hussain, Amjad; Rauf, Abdur; Hussain, Wahid; Ullah, Manzoor; Abbas, Safdar; Al-Awthan, Yahya S.; Bahattab, Omar; Khan, Muhammad; Olatunde, Ahmed; Almarhoon, Zainab M.; et al.
Abstract : Investigation on medicinal plants' therapeutic potential has gained substantial importance in the discovery of novel effective and safe therapeutic agents. The present study is aimed at investigating the hepatoprotective potential of Seriphidium kurramense methanolic extract (SKM) against carbon tetrachloride- (CCl4 -) induced hepatotoxicity in rats. S. kurramense is one of the most imperative plants for its various pharmacological activities. Therefore, this study was aimed at evaluating the hepatoprotective potential against CCl4 -induced liver toxicity. The serum samples were analyzed for alanine aminotransferase (ALT) and aspartate aminotransferase (AST) together with the oxidative stress mediator levels as nitric oxide (NO), malondialdehyde (MDA), glutathione (GSH), reduced glutathione (GSH), and superoxide dismutase (SOD) as well as peroxidation and H2 O2 activity. CCl4 administration resulted in an elevated free radical generation, altered liver marker (AST and ALT) enzymes, reduced antioxidant enzyme, and increased DNA damage. Methanolic extract of S. kurramense decreased CCl4 -induced hepatotoxicity by increasing the antioxidant status and reducing H2 O2 and nitrate content generation as well as reducing DNA damage. Additionally, SKM reversed the morphological alterations induced by CCl4 in the SKM-treated groups. These results demonstrated that SKM displayed hepatoprotective activity against CCl4 -induced hepatic damage in experimental rats.